Sistem Instalasi Listrik Sebagai Sarana Penerangan Laboratorium Terpadu Universitas Sultan Ageng Tirtayasa - Uus Ustiyaroh; Irwanto Irwanto (LPPM Institut Nasional Laa Roiba Bogor, 2022)
The use of electrical energy consumed by the University of Sultan Ageng Tirtayasa uses electrical energy sources managed by PLN which are included in primary consumers, where primary electricity customers are given a voltage of 20kV (medium voltage). Then from the PLN substation in Untirta, it is distributed by equipment or components to the Sultan Ageng Tirtayasa University area. Medium Voltage (TM) which is a strong current at Sultan Ageng Tirtayasa University is divided into 5 parts, where the medium voltage starts from the power house and enters the Integrated Laboratory Building, Economic Building, Transformer House, Integrated Class and Rectorate Building. The light voltage (TR) is divided into 3 zones, namely the Integrated Laboratory Building, Transformer House and Rectorate Building. The research method used is qualitative research with a descriptive approach. Data collection techniques used are observation, interviews, documentation, and literature study. Analysis of the data used is interactive analysis by Milles & Humerman. The results of the study stated that this light voltage is used as an additional voltage to compensate for medium voltages such as lighting lamps. The lighting source in the Integrated Laboratory uses the Philips brand with 5 types of lamps namely TL-LED, LED Floodlight, LED BULB, BL CG TL-5 and TL-RM 300 M1 which have IP Ratings of IP65 and IP20. For output use 10-200watt with a lighting level of 2100-28000 lm. The Schneider brand socket has a power of 200-1000 watt and a current of 16 Ampere. Keywords: installation, system, lighting, building, laboratory, facilities.